Pengembangan UMKM Berbasis Website Pada Dusun Teluk Pandak Kecamatan Tanah Sepengkal Kabupaten Bungo - Amin Albadry, Syah; Alam, Sandi; Nasir, H.Muhammad; Antoni , Feri; Darmawanto, Darmawanto; Jesika, Silvia; Zulkifli, Zulkifli; Feni Astari, Hasdani (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
The problems faced by Teluk Pandak Kecamatan Tanah Sepengkal Kabupaten BungoKecamatan Tanah Sepengkal Kabupaten BungoUMKM are related to entrepreneurial abilities that need to be developed in entrepreneurs. Therefore, it is important to carry out Community Service (PKM) to solve this problem. The target (specifically) of this service is to provide solutions through socialization and creation of village websites and village UMKM. The aim of this program is to provide an understanding of entrepreneurial skills to UMKM entrepreneurs, to educate them on taking advantage of existing opportunities with the use of digital technology which is developing rapidly at this time in order to be able to improve welfare, not only in terms of material things, but the welfare of a creative, innovative mindset, and independent. The results of this program include, among others, that these UMKM can form an even larger network by utilizing technology and other digital technology Village Websites which are increasingly developing in the era of industrial revolution 4.0, era of society 5.0. In the future, training via this website should be able to provide rapid progress for UMKM, especially in Teluk Pandak Kecamatan Tanah Sepengkal Kabupaten BungoKecamatan Tanah Sepengkal Kabupaten BungoHamlet, Tanah Sepengkal District, and the products produced will be more diverse and sought after by various groups.